2016
DOI: 10.1016/j.anucene.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo power iteration: Entropy and spatial correlations

Abstract: The behaviour of Monte Carlo criticality simulations is often assessed by examining the convergence of the so-called entropy function. In this work, we shall show that the entropy function may lead to a misleading interpretation, and that potential issues occur when spatial correlations induced by fission events are important. We will support our analysis by examining the higher-order moments of the entropy function and the center of mass of the neutron population. Within the framework of a simplified model ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Recently the phenomenon of neutron clustering has been shown to strongly affect Monte Carlo burn-up simulations (Dumonteil et al, 2014;Zoia et al, 2014;de Mulatier et al, 2015;Nowak et al, 2016;Sutton and Mittal, 2017;Cosgrove et al, 2019). Minimising its effects entails simulating large numbers of neutrons per cycle for fewer cycles (Dumonteil et al, 2014;Sutton and Mittal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the phenomenon of neutron clustering has been shown to strongly affect Monte Carlo burn-up simulations (Dumonteil et al, 2014;Zoia et al, 2014;de Mulatier et al, 2015;Nowak et al, 2016;Sutton and Mittal, 2017;Cosgrove et al, 2019). Minimising its effects entails simulating large numbers of neutrons per cycle for fewer cycles (Dumonteil et al, 2014;Sutton and Mittal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, for either of the relations presented, when increasing the height of, say, a fuel pin problem, increasing the number of particles simulated per generation (or the number of generations) to ensure a constant particle density per unit length is insufficient: clustering will occur eventually unless particle numbers increase superlinearly with the characteristic dimension. This point has been made by some of the authors mentioned above (and is demonstrated by Nowak et al (2016)) but should be emphasised in the context of depletion: for some users, intuition might incorrectly suggest that a 4 m pin with 10 burnable regions might not even require as many particles as a 2D 17-by-17 PWR assembly, which will typically have many more burnable regions. The work by Sutton and Mittal (2017) provides another important insight for clustering in Monte Carlo simulations: using excessively many particle generations can worsen the results obtained.…”
Section: Monte Carlo Neutron Clusteringmentioning
confidence: 99%
“…For a PWR, the migration area is about 56 cm 2 , giving, for a 4 m pin, an N 0 on the order of 10,000. This particular scaling relation was investigated by Nowak et al (2016) for a series of geometries, including a 4 m reflected PWR pin. It was shown that on the order of 500,000 particles per generation were adequate for modelling the problem.…”
Section: Monte Carlo Neutron Clusteringmentioning
confidence: 99%
“…For convergence to happen, it is first necessary to check that the fission source distribution (FSD) used by the Monte Carlo code MCS at the beginning of each coupled step has reached stationarity. For that purpose, a given number of inactive coupled cycles are run, during which the FSD stationarity is checked by studying the evolution of the Shannon entropy [34], the centerof-mass of the FSD (center-of-mass of the weighted fission sources) [35] and the axial offset as a function of the number of inactive coupled cycles. The Shannon entropy of the fission distribution is calculated with a mesh of 10-cm-side cubes superimposed on the MHTGR-350 active core.…”
Section: Convergence Criteriamentioning
confidence: 99%